Sensitivity, specificity and negative predictive value of two low-risk stratification rules in patients presenting with pulmonary embolism - Palas, Miguel João Soares (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021